The performance of single mother co-operatives and their influencing factors : a qualitative investigation in Peninsular Malaysia - Azliana Mohd Jelani; Muhammad Hakimi Mohd Shafiai; Nurul Syazwani Mohd Noor (Penerbit Universiti Kebangsaan Malaysia, 2021)
The purpose of this study is to investigate the performance of Peninsular Malaysia’s single mother co-operatives. This study mainly examines the number of active and inactive co-operatives and identifies the key factors influencing their success or failure. The research evaluated 23 co-operative groups of single mothers. The performance of the cooperatives was analysed through in-depth interviews with officers of the Malaysian Co-operative Societies Commission (MCSC). Despite the government’s financial and non-financial assistance, the findings indicate that cooperatives have not performed well. The preliminary results suggest that inactive single mother co-operatives are higher than those active ones. This study found that 61% of the total single mother co-operatives in Peninsular Malaysia are inactive (dormant and non-operational) compared to 39% active ones. Four influencing factors contribute to a higher percentage of inactive co-operatives: limited resources, dependence on subsidies and sponsors, managerial incompetency, and member participation. The results suggest solutions for the management of single mother co-operatives and provide additional information and contribution to the parties involved to empower the association to fulfil the economic, social, and cultural requirements.